Identification of Vehicle Through Video Motion using Haar Cascade Classifier - Sangeetha M,Sagana C, Manjula Devi R,Naveen Kumar S , Pavithran P; Ponnarasu R (International Journal of Control and Automation, 2020)
To reduce the congestion in the road and to make improve the traffic parameters in the road lanes. Smarter ways are developed for analysing traffic and to take a appropriate solution. Analysis of traffic is the process to identify or to count the number of vehicles in a particular time period. So peoples are developing the solutions for the problem but most of them were involved by sensors. Even though this gives a good solution but this are not budget friendly one. This paper the methodology followed here is counting the number of vehicles from the video ,this involves three process they are analysing ,identifying and counting the result. For this the algorithm we proposed is Haar Cascade Classifier for identifying vehicles. The identification can be done in straight lane ,cross lane and in the T-junction traffic areas.